2020
DOI: 10.1111/tbed.13682
|View full text |Cite
|
Sign up to set email alerts
|

Use of a demonstration project to evaluate viral survival in feed: Proof of concept

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Foreign animal diseases, such as African swine fever virus (ASFV), pose a significant threat to the United States pork industry because contaminated feed ingredients, pork products, and humans can all be potential sources of disease introduction (Dee et al, 2014;Álvarez et al, 2019;Niederwerder et al, 2019;Dee et al, 2020a). Some RNA viruses such as Seneca virus A (SVA), Porcine reproductive and respiratory syndrome virus (PRRSV), and Porcine epidemic diarrhea virus (PEDV), have been shown to survive in feed ingredients and infect pigs under experimental conditions (Dee et al, 2014;Niederwerder et al, 2019;Dee et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign animal diseases, such as African swine fever virus (ASFV), pose a significant threat to the United States pork industry because contaminated feed ingredients, pork products, and humans can all be potential sources of disease introduction (Dee et al, 2014;Álvarez et al, 2019;Niederwerder et al, 2019;Dee et al, 2020a). Some RNA viruses such as Seneca virus A (SVA), Porcine reproductive and respiratory syndrome virus (PRRSV), and Porcine epidemic diarrhea virus (PEDV), have been shown to survive in feed ingredients and infect pigs under experimental conditions (Dee et al, 2014;Niederwerder et al, 2019;Dee et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of long-distance truck transport of virus-inoculated feed ingredients and complete feed in the U.S. have also been evaluated. Dee et al [50] conducted a demonstration study to determine if viable and infectious PRRSV, PEDV, and SVV-A would survive a 21-day commercial truck transport for more than 9000 km across 14 states in the U.S. when a mixture of these viruses was inoculated in organic and conventional soybean meal, L-lysine HCl, choline chloride, and vitamin A. All viruses were detected as infectious in soybean meal, while infectious SVV-A was found in L-Lysine HCl and vitamin A.…”
Section: Virus Survival In Feed Ingredients During Transportmentioning
confidence: 99%
“…Using the same experimental design and 23-day commercial U.S. truck transport model, Dee et al [25] showed that inoculation of conventional soybean meal, organic soybean meal, and conventional feed with PRRSV, PEDV, and SVV-A resulted in all viruses remaining infective at the end of the transport period based on pig bioassays. In addition, a surrogate virus (Emiliania huxleyi virus or EhV) for ASFV was used to inoculate conventional and organic soybean meal and swine complete feed to simulate an ASFV contamination event [51] using the same experimental design as described by Dee et al [50]. Results showed that viable EhV was detected in all matrices at the end of the transport period, and no degradation of viability occurred.…”
Section: Virus Survival In Feed Ingredients During Transportmentioning
confidence: 99%
“…It has only been since the outbreak of the porcine epidemic diarrhea virus in the United States in 2013 that feed as a carrier vehicle for viral pathogens has been established (19,20). Yet, since then there has been overwhelming evidence that pathogens, including PRRSV, survive in feed and pigs can be infected following consumption of contaminated feed (21,22). In an effort to mitigate this threat, a variety of feed additives, such as acids or formaldehyde solutions, have been experimentally evaluated and found effective at reducing PRRSV transmission to pigs in feed (23) after multiple experimental studies showed their effectiveness in reducing the risk of porcine epidemic diarrhea virus transmission, as well as several other viruses (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%